THE EVOLUTION OF THE EUROPEAN COMMUNITIES TOWARDS THE EUROPEAN UNION IN THE LIGHT OF THE REFORM TREATIES - Florentina Trif (Romanian Journal of Historical Studies)
The European project embodied in the European Union (EU) today is in a continuous process of development, a process that has lasted over six decades. Throughout this period, the development of the European Communities has been marked by two main directions: on the one hand, the enlargement by the accession of new Member States and, on the other, by the adoption of reform treaties to ensure the good functioning of the European Communities. Based on these premises, the importance of this study lies in identifying and highlighting the reforms implemented by each treaty. In this regard, the objectives are to analyze the post-war situation on the European continent and the historical context in which the European Communities have been established, as well as to analyze the complex evolution of the Community system, with a focus on clarifying aspects related to the establishment of the European Union by analyzing the provisions of the Modifying Treaties